Measurement of sand moisture composition for concrete mixture - Nur Aqilah, Othman; Hamzah, Ahmad; Mohd Hasnun Ariff, Hassan; Wan Muhammad Syamim, Wan Ahmad Puzi (Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka (UTeM), 2018)
This study proposes a measurement device that monitors the volume of water in wet sand. The aim is to control the amount of water in the concrete mixture from over-watered sand that would affect the balance concrete mixture ratio during construction process. The proposed system would increase the quality of concrete produced. The system was programmed using a micro-controller to send an interrupt signal to the monitoring system depending on the soil moisture levels. The soil moisture/humidity levels are checked using soil moisture sensor. Whenever there is a change in moisture/humidity in the soil, the sensor sends an interrupt signal to the micro-controller and the data will be fed to the monitoring software.